2021
DOI: 10.3390/ijms22179290
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitors in the Treatment of Neurodegenerative Diseases and the Role of Acetylcholinesterase in their Pathogenesis

Abstract: Acetylcholinesterase (AChE) plays an important role in the pathogenesis of neurodegenerative diseases by influencing the inflammatory response, apoptosis, oxidative stress and aggregation of pathological proteins. There is a search for new compounds that can prevent the occurrence of neurodegenerative diseases and slow down their course. The aim of this review is to present the role of AChE in the pathomechanism of neurodegenerative diseases. In addition, this review aims to reveal the benefits of using AChE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 539 publications
(569 reference statements)
1
67
0
Order By: Relevance
“…DPP4 inhibitors have been shown to control blood glucose levels and prevent the exacerbation of cognitive impairment in older type 2 diabetes patients with mild cognitive impairment [ 52 ]. Acetylcholinesterase (AChE) is involved in inflammatory reactions, neuronal apoptosis, oxidative stress and the aggregation of pathological proteins, which are closely related to the pathogenesis of neurodegenerative diseases [ 53 ]. Studies have shown that low doses of donepezil (2.5 mg/d) can improve cognitive function, especially memory function, in patients with aMCI [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPP4 inhibitors have been shown to control blood glucose levels and prevent the exacerbation of cognitive impairment in older type 2 diabetes patients with mild cognitive impairment [ 52 ]. Acetylcholinesterase (AChE) is involved in inflammatory reactions, neuronal apoptosis, oxidative stress and the aggregation of pathological proteins, which are closely related to the pathogenesis of neurodegenerative diseases [ 53 ]. Studies have shown that low doses of donepezil (2.5 mg/d) can improve cognitive function, especially memory function, in patients with aMCI [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases can include Alzheimer’s Disease (AD), PD, and multiple sclerosis (MS) [ 147 , 148 , 149 , 150 ]. These diseases usually lead to the degeneration of the nervous system by different mechanisms depending on the disease.…”
Section: Beneficial Properties Of Sodium Benzoatementioning
confidence: 99%
“…As shown in Table 6, compound 1 seems to be the most active on the nervous system by targeting key enzymes named acetylcholinesterase (Pa = 0.292) and butyrylcholinesterase (Pa = 0.219) in a non-negligible way, which suggests that this compound could actively participate in the regulation of the activity of these two enzymes known for their important roles in cholinergic transmission by facilitating the hydrolysis of acetylcholine (ACh) neurotransmitter [103]. On the other hand, compound 1 may also participate with other compounds ina synergistic way to limit the activity of these enzymes, since an excessive activity of acetylcholinesterase may lead in the long term to neurodegenerative illnesses such as Alzheimer's and Parkinson's diseases [104]. A key receptor called muscarinic acetylcholine receptor (M1) could be also targeted by this compound (Pa = 0.175), and several studies [105,106] reported the crucial role of this receptor during learning and memory processes, but it could also be a promising therapeutic target for the improvement of cognitive decline in Alzheimer's disease (AD).…”
Section: Macromolecular Targets Predictionmentioning
confidence: 99%